Faktor-Faktor Yang Mempengaruhi Mahasiswa Pendidikan Ekonomi Terhadap Memilih Jurusan Pendidikan Ekonomi - Djailani, Yulan; Sudirman, Sudirman; Damity, Fatmawati; Ardiansyah, Ardiansyah; Halid, Risca Marsanti (Gorontalo State University, 2026)
This study aims to determine the influence of program image, career prospects, and accreditation on students' decisions to choose the Economics Education Program in the Faculty of Economics and Business, Universitas Negeri Gorontalo.A quantitative approach was used in this study. Primary data were collected through questionnaires distributed to the 2024 cohort of Economics Education students, with a total sample of 66 respondents. Data analysis was conducted using multiple linear regression with IBM SPSS Statistics version 21.0. Based on the analysis and discussion, the factor significantly influencing Economics Education students in choosing the program is the program image. The partial statistical test (t-test) for the program image variable (X1) yielded a t-count t-table of 2,549 1,998, with a significance level of 0,013 (0.05), indicating that the hypothesis stating